An Outbreak of Kawasaki-like Disease in children during SARS-CoV- 2 Epidemic: No Surprise? - Cavallo, Federica; Chiarelli, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Kawasaki disease is an acute systemic febrile illness of unknown aetiology, which usually affects children under 5 years of age. It is well known that Kawasaki disease is one of the most common causes of acquired heart diseases in children in the developed countries. Many studies, have suggested that heterogeneous infectious agents, such as common viruses, may trigger Kawasaki disease in young children with genetic background. Nowadays we are facing a pandemic caused by a Novel Coronavirus named SARS-CoV-2. Consequently, it could be possible that once exposed to this new coronavirus, some children, genetically predisposed, may mount an exaggerated inflammatory response which clinically manifests as Kawasaki Disease. Methods: from January to May 2020 a systematic search was performed on Pubmed for the following search terms: “COVID-19”, “children”, “SARS-CoV-2”, “complications”, “Kawasaki disease”, “cytokine storm”. Results: Usually, infants and children present milder symptoms of SARS-CoV-2 disease with a better outcome than adults. At variance, some children may be genetically disposed to a more robust inflammatory response to SARS-CoV-2, similar to Kawasaki disease. In fact, Kawasaki disease is the result of an abnormal immune response, in susceptible children, to an external trigger such as an infection. Thus, according to the pathogenesis of Kawasaki disease, paediatricians may expect an increase in cases of Kawasaki disease during the COVID-19 pandemic.